2021
DOI: 10.3389/fmicb.2021.594631
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanisms of L-Lactic Acid and Taste Substances in Chinese Acid Rice Soup (Rice-Acid) Fermented With a Lacticaseibacillus paracasei and Kluyveromyces marxianus

Abstract: Rice-acid has abundant taste substances and health protection function due to the various bioactive compounds it contains, including organic acids. L-lactic acid is the most abundant organic acid in rice-acid, but the regulatory mechanisms of L-lactic acid accumulation in rice-acid are obscure. In this study, we analyzed the dynamic changes in organic acids and taste substances in rice-acid in various fermentation phases and different inoculation methods. We identified the key genes involved in taste substance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Out of 393 metabolites, 144 different metabolites were identified and mainly included amino acids and their derivatives, nucleotides and their derivatives, alkaloids, sugars and alcohols, phenolic acids, organic acids, and other secondary metabolites. Previous studies have also shown that taste substances in the inoculated group were more abundant and the intensity of the sourness was highest owing to the dynamics from saccharification to alcoholization and acidification in the fermentation process of foods inoculated with LAB and yeasts [27,28]. A recent study reported the correlation between microbial communities (bacterial and fungal) and important volatile metabolites in red pepper (Capsicum annuum L.) fermentation [29].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Out of 393 metabolites, 144 different metabolites were identified and mainly included amino acids and their derivatives, nucleotides and their derivatives, alkaloids, sugars and alcohols, phenolic acids, organic acids, and other secondary metabolites. Previous studies have also shown that taste substances in the inoculated group were more abundant and the intensity of the sourness was highest owing to the dynamics from saccharification to alcoholization and acidification in the fermentation process of foods inoculated with LAB and yeasts [27,28]. A recent study reported the correlation between microbial communities (bacterial and fungal) and important volatile metabolites in red pepper (Capsicum annuum L.) fermentation [29].…”
Section: Discussionmentioning
confidence: 95%
“…These findings indicated that amino acid metabolism is not only the starting point for the synthesis of various metabolites such as glycine, cysteine, and serine phospholipids but also supplies essential amino acids for protein synthesis [37]. Moreover, most amino acids are essential metabolites that are required for the growth and protein synthesis of LAB in the fermentation process [28]. Our findings also indicated that mixed inoculation of different LAB strains exhibited synergistic effects on the fermentation process and production of metabolites, which is in agreement with earlier studies [28].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These include a complete cluster for F0-F1 ATPase proton pump, that regulates cytoplasmic pH by pumping out H + after ATP hydrolysis ( Deckers-Hebestreit and Altendorf, 2003 ), as well as a sodium: proton antiporter for sodium and pH homeostasis ( Huang et al, 2016 ). I t should be noted that acid tolerance can be manifested in a plethora of ways, including cell wall modifications and biofilm formation ( Liu et al, 2021 ). In this context, biofilm formation supports survival and proliferation in hostile environments, as viable bacteria are protected in a polysaccharidic capsule ( Liu et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…I t should be noted that acid tolerance can be manifested in a plethora of ways, including cell wall modifications and biofilm formation ( Liu et al, 2021 ). In this context, biofilm formation supports survival and proliferation in hostile environments, as viable bacteria are protected in a polysaccharidic capsule ( Liu et al, 2021 ). Genes implicated in biofilm formation, such as luxS and comC , comD and comE , were also annotated.…”
Section: Resultsmentioning
confidence: 99%